Tools for monitoring toxicological and genotoxicological changes in a drinking water treatment plant in Northeast Italy. (26th August 2022) - Alias, Carlotta; Feretti, Donatella; Benassi, Laura; Zerbini, Ilaria; Zani, Claudia; Sorlini, Sabrina
Abstract: Drinking water quality can be compromised at different stages, from raw water to treated one. This research aimed to evaluate the toxicity and genotoxicity of groundwater contaminated by fluorinated compounds treated in a drinking water treatment plant, through several bioassays. Water samples underwent chemical analyses and were assayed on Daphnia magna, Pseudokirchneriella subcapitata, Allium cepa, human leukocytes and Salmonella typhimurium . Physical–chemical parameters were always within the Italian legislation limits. Water after filtration and disinfection caused slight toxicity in D. magna ; the sample after filtration inhibited the proliferation of P. subcapitata . None of the water samples exerted toxicity in A. cepa . All the analysed samples had genotoxic effects on A. cepa and human leucocytes, while only disinfected water caused mutations in S. typhimurium . A battery composed of tests on D. magna, P. subcapitata, S. typhimurium and A. cepa could represent a useful tool to verify the toxicity/genotoxicity through the water treatment stages and to improve drinking water quality management.